Angiotensin II Activates Na+-Independent Cl−-HCO3− Exchange in Ventricular Myocardium - Camilión de Hurtado, María Cristina (1998)
The effect of angiotensin II (Ang II) on the activity of the cardiac Na+-independent Cl−-HCO3− exchanger (anionic exchanger [AE]) was explored in cat papillary muscles. pHi was measured by epifluorescence with BCECF-AM. Ang II (500 nmol/L) induced a 5-( N -ethyl- N -isopropyl)amiloride–sensitive increase in pHi in the absence of external HCO3− (HEPES buffer), consistent with its stimulatory action on Na+-H+ exchange (NHE). This alkalinizing effect was not detected in the presence of a CO2-HCO3− buffer (pHi 7.07±0.02 and 7.08±0.02 before and after Ang II, respectively; n=17). Moreover, in Na+-free HCO3−–buffered medium, in which neither NHE nor Na+-HCO3− cotransport are acting, Ang II decreased pHi, and this effect was canceled by previous treatment with SITS. These findings suggested that the Ang II–induced activation of NHE was masked, in the presence of the physiological buffer, by a HCO3−-dependent acidifying mechanism, probably the AE. This hypothesis was confirmed on papillary muscles bathed with HCO3− buffer that were first exposed to 1 μmol/L S20787, a specific inhibitor of AE activity in cardiac tissue, and then to 500 nmol/L Ang II (n=4). Under this condition, Ang II increased pHi from 7.05±0.05 to 7.22±0.05 ( P <.05). The effect of Ang II on AE activity was further explored by measuring the velocity of myocardial pHi recovery after the imposition of an intracellular alkali load in a HCO3−-containing solution either with or without Ang II. The rate of myocardial pHi recovery was doubled in the presence of Ang II, suggesting a stimulatory effect on AE. The enhancement of the activity of this exchanger by Ang II was also detected when the AE activity was reversed by the removal of extracellular Cl− in a Na+-free solution. Under this condition, the rate of intracellular alkalinization increased from 0.053±0.016 to 0.108±0.026 pH unit/min (n=6, P <.05) in the presence of Ang II. This effect was canceled either by the presence of the AT1 receptor antagonist, losartan, or by the previous inhibition of protein kinase C with chelerythrine or calphostin C. The above results allow us to conclude that Ang II, in addition to its stimulatory effect on alkaline loading mechanisms, activates the AE in ventricular myocardium and that the latter effect is mediated by a protein kinase C–dependent regulatory pathway linked to the AT1 receptors.